Evaluation of the effect of tooth polishing on color stability after in-office bleaching treatment - Luís Felipe ESPÍNDOLA-CASTRO; Pamella Robertha Rosselinne Paixão CELERINO; Tácyla Alves do NASCIMENTO; Gabriela Queiroz de Melo MONTEIRO; Tereza Cristina CORREIA (Universidade Estadual Paulista, 2020)
Abstract Introduction One of the most commonly used corrective methods for staining teeth is tooth bleaching. However, subclinical alterations may occur in the micromorphology of dental tissues during the bleaching procedure, such as increases in porosity and surface roughness. Consequently, dental enamel may become more permeable and susceptible to staining. Objective To evaluate the influence of tooth polishing after in-office bleaching treatment on color stability. Material and method Thirty-three extracted human molars were used. The teeth were cut in the mesiodistal direction to obtain two samples per tooth (total of 66). The samples were randomly divided into six groups (n=11). Before and after the bleaching treatment, the lightness of the samples and change in lightness (∆L) were determined with a digital spectrophotometer (Easy Shade). The samples were bleached with 35% hydrogen peroxide (three sessions weekly). Three groups were submitted to polishing with felt discs and polishing paste after each session. To simulate the oral conditions during the consumption of colored beverages, the samples were submitted to alternating cycles of immersion in staining solutions (coffee, red wine, and Coca Cola). Result Polishing resulted in an increase of mean lightness of 4.49 in the red wine group, 2.73 in the coffee group, and 4.08 in the cola group. The difference was significant in the red wine group (p<0.022), but not in the coffee or cola group. Conclusion Polishing after in-office bleaching using felt discs and polishing paste can reduce the degree of pigment impregnation in patient with red wine rich diet.